Difusi Polifenol dari Krim Ekstrak Daun Kelor (Moringa oleifera) dengan Peningkat Penetrasi Dimethyl Sulfoxide (DMSO): Diffusion of Polyphenols from Moringa oleifera (Moringa oleifera) Leaf Extract Cream with Dimethyl Sulfoxide (DMSO) Penetration Enhancer - Andi Rezki Khaerun Nissa; Arisanty Arisanty; Nurisyah Nurisyah (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Moringa leaves are one of the plants that contain polyphenolic compounds so that they have the potential to be made cream preparations. In addition, cream preparations should have substances that are efficacious as penetration into the skin. This study was conducted to find out how DMSO as a penetration enhancer affects the penetration and diffusion of polyphenols in Moringa leaf extract cream. The cream is made with 4 formulations, each formula has DMSO concentration variations of 0%, 15%, 20%, and 25%. Diffusion testing by Moringa leaf cream using Franz Diffusion cells and diffusion membranes in the form of cellophane membranes. Based on the results of the study that F2 with a DMSO concentration of 20% showed the highest diffusion of polyphenols, the highest cumulative amount of penetrated polyphenols and the best polyphenol release profile. The results of statistical analysis using One Way ANOVA show that F2 and F3 have significance (p < 0.05) compared to F0 without penetration. Keywords: Diffusion Polyphenols, Creams, Moringa Leaves, Penetration Enhancers Abstrak Daun Kelor merupakan salah satu tanaman yang mengandung senyawa polifenol sehingga berpotensi dibuat sediaan krim. Disamping itu, sediaan krim sepatutnya mempunyai zat yang berkhasiat sebagai penetrasi menembus ke dalam kulit. Penelitian ini dilakukan untuk mengetahui bagaimana DMSO sebagai peningkat penetrasi mempengaruhi penetrasi dan difusi polifenol pada krim ekstrak daun kelor. Krim dibuat dengan 4 formulasi yang tiap formulanya memiliki variasi konsentrasi DMSO 0%, 15%, 20%, dan 25%. Pengujian difusi oleh krim daun kelor menggunakan sel Difusi Franz serta membrane difusi berupa membrane selofan. Berdasarkan hasil penelitian bahwa F2 dengan konsentrasi DMSO 20% menunjukkan difusi polifenol tertinggi, jumlah kumulatif polifenol terpenetrasi tertinggi dan profil pelepasan polifenol terbaik. Hasil analisis statistic menggunakan One Way ANOVA menunjukkan bahwa F2 dan F3 memiliki signifikansi (p < 0,05) dibanding F0 tanpa penetrasi. Kata Kunci: Difusi Polifenol, Krim, Daun Kelor, Peningkat Penetrasi